Are there any volatility spill-over effects among cryptocurrencies and widely traded asset classes? - Nader Trabelsi (Journal of Risk and Financial Management, 2018)
In the present paper, we investigate connectedness within cryptocurrency markets as well as across the Bitcoin index (hereafter, BPI) and widely traded asset classes such as traditional currencies, stock market indices and commodities, such as gold and Brent oil. A spill over index approach with the spectral representation of variance decomposition networks, is employed to measure connectedness. Results show no significant spillover effects between the nascent market of cryptocurrencies and other financial markets. We suggest that cryptocurrencies are real independent financial instruments that pose no danger to financial system stability. Concerning the connectedness within the cryptocurrency markets, we report a time-frequency-dynamics connectedness nature. Moreover, the decomposition of the total spill over index is mostly dominated by a short frequency component (2-4 days) leading to the conclusion that this nascent market is highly speculative at present. These findings provide insights for regulators and potential international investors.
Keywords: 330; cryptocurrencies; connectedness; spill overs; spectral analysis; time-frequency-dynamic